REVISIONISME MARXISME DAN PERKEMBANGAN IDEOLOGI DEMOKRASI SOSIAL (STUDI PEMIKIRAN EDUARD BERNSTEIN DAN ANTHONY GIDDENS) - Warganegara, Arizka (Universitas Riau, 2011)
This study is about the law development of social democracy in the perspective of Eduard Bernstein andAnthony Giddens. It applied the method of qualitative analysis and used the library research, the data inthis study analyzed with the content of analysis. The main purposes of this study wants to describe andanalysis of Law Development of Social Democracy in the perspective of Bernstein and Giddens.Socialism Democracy of Bernstein and Cosmopolitan Democracy of Giddens used as toll of comparative.Social Democracy has been revision three times, Bernstein is the first generation, The second generationis Social Democratic Party of Germany with The bad Godesberg Program and the last is Giddens. Theinteresting of this study is the basic difference among Bernstein and Giddens in the understanding ofconcept of Social Democracy. The different time and context imply the different ontology andepistemology to this ideology. If Bernstein lived in the time of raised of capitalism and Industrialization inEurope, Giddens has lived in the time of this ideology must be against the raises of Neo liberalism andGlobalization. Actually The basic concept of Social democracy of Bersntein is his critics to the theory andconcept of Karl Marx, this causes the different perspective with Giddens. Finally Giddens made thisideology more Liberal than before, many political scientist assume that The Third Way of Giddens is thecontinuously of Capitalism.Keywords : Social Democracy, Bad Godesberg and Capitalism